A study of otorhinolaryngological diseases with ophthalmic complications: at a tertiary care center - Gobind, Adhira; Sachdeva, Kavita (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2022)
Background: The close proximity of the eyeball and the orbit to the ENT region, makes the involvement of the orbit and there of ophthalmological manifestations common in the practise of Otorhinolaryngology. The diseases of ENT with orbital extension must be considered whenever a patient presents with signs and symptoms of orbital disease such as proptosis, orbital mass, restriction of eye movements, neurological dysfunction of eye, chemosis, vision disturbances or epiphora. Methods: Patients presenting with ophthalmological manifestations due to various ear, nose, throat and head–neck pathologies were constituted in this prospective study which was carried out on 50 patients of the age group 10 years to 60 years with ophthalmological complications along with ENT diseases who came to the department of ENT and department of Ophthalmology of N.S.C.B. Medical College, Jabalpur from August 2019 to August 2021. Results: Males were affected more than female with ophthalmic complications. Sinonasal tumours were the most common cause of orbital complications, of which carcinoma of maxilla was the commonest , followed by sinonasal lymphoma .Nasal obstruction was the most common ENT complaint and proptosis was the commonest orbital sign. Conclusions: A firmer knowledge of orbital anatomy with respect to sinonasal region is required for any surgeon dealing with this important area, for a safer and more secure management in this complex region. Surgery remains the main stay of treatment for sinonasal diseases with orbital complications. Rapid diagnosis and treatment are of utmost importance in preserving vision and life in these patients.